Factibilidad económica de los programas de intervención ergonómica del factor seguridad, carga y diseño físico en el área de Agrícola, ESPAM-MFL - Cepeda Guacho, Ruth Maribel (2015)
The aim of the research was to analyze the economic feasibility of ergonomic intervention programs of the security factor, loading and physical design in the career of Agricultural of ESPAM-MFL, for this we applied a method to assess the socio-economic impact. Stages I describes the current status of jobs through a check list that was aimed coordinators / technicians and workers of different units: phase thel consist of 4 steps of which the first two were applied to meet existing gaps in each one, then a matrix was designed to describe the causes and consequences of the problems encountered and estimate the magnitude of risk by weighting through kendall method by experts or knowledgeable about the situation. It was also necessary to apply the matrix method was made in order to evaluate the risk factors perceived by the company and employees; in stage II ergonomic improvement and an investment plan which detailing corrective action based on relevant problems in each risk factor and thus estimate the cost of these actions, thus contributing to increased the company´s productivity and improve the quality of working life in each of the jobs. Finally the results obtained from the competent authorities to the problem were socialized.